THE EFFECT OF METHANOL EXTRACT OF MANGO LEAF WITH CMC AND PEG ON AEDES AEGYPTI LARVAE MORTALITY - BESTARI, ROCHMADINA S.; TRIHATMOKO, FAHRIZA M.; SINTOWATI, RETNO; DEWI, LISTIANA M.; ROSYIDAH, DEVI U. (International Journal of Applied Pharmaceutics, 2025)
Objective: This research aims to determine the effectiveness of mango leaf methanol extract (Mangifera indica L.) with Carboxymethyl Cellulose (CMC) and Polyethylene Glycol (PEG) diluents on the mortality of Aedes aegypti larvae. CMC and PEG are used to increase the effectivity of mango leaf extract as larvicide. Methods: Research on methanol extract of mango leaves (Mangifera indica L.) with CMC and PEG diluents has an experimental laboratory design with a posttest-only controlled group design. The technique of extraction is maceration. The larvae of Aedes aegypti instar III-IV are used, 700 in total, divided into 7 treatment groups. Results: The Lethal Concentration (LC50) result of the extract with CMC diluent at the 24th hour was 0.114%, while the LC50 of the extract with PEG diluent was 0.323%. The Lethal Time (LT50) of 0.05% concentration of extract with CMC diluent is 294.755 h and PEG with 140.764 h. At a concentration of 0.1% with CMC diluent is 195.267 h and PEG 194.630 h. Conclusion: Methanol extract of mango leaf (Mangifera indica L.) with CMC and PEG diluents is effective on mortality of Aedes aegypti larvae. CMC-diluted extract demonstrated 2.8-fold higher potency (LC50: 0.114%) than PEG-diluted extract (LC50: 0.323%). CMC need lower concentration than PEG so it can be effective due to lower funding and the environment effect.